Political Economy of Land Use in Indonesia: Trap and Curse of Natural Forests - Sudarsono Soedomo (Jurnal Manajemen Hutan Tropika, 2021)
The allocation of land use in Indonesia is very ineﬃcient, while the distribution of tenure is unequal. Half of the land for cultivation is held by forestry, and the other half is used by various other sectors. Most Indonesian farmers are small- scale farmers who do not meet economies of scale. Agrarian reforms aimed at overcoming ineﬃciency in land use, eliminating inequality in land tenure, and promoting rural areas’ prosperity need to involve land for cultivation allocated for forestry. This paper is written based on the author’s experience of interacting with various parties related to land issues, forest areas and agrarian reform through various forums, such as oﬃcial meetings, focus group discussions, seminars, workshops, symposiums, one-on-one discussions (interviews), and interactions through social media. Agrarian reform, which has been launched since 1960, has not been able to be realized until today. The fight seems to involve two large groups, namely environmentalists and developmentalists, but this kind of grouping is likely to be misleading. Environmental issues may only be used as an instrument to obtain economic benefits as well, not for the environment itself.